L’attitude des élèves de lycée en d’apprentissage de la langue française - Dicky Sudarmaji; Diah Vitri Widayanti (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2024)
French is one of the foreign languages ​​studied by high school students. Based on data in Semarang, as of 2017, 14 schools applied French language learning, but in 2019, it was reduced to 10 schools. One of the reasons was the lack of student’s interest in learning French, thus forming unexpected attitudes. Based on this problem, I tried to find out how students behave when learning French. The research method of this study is descriptive quantitative. The object of this study is high school students in 10th and 11th grade. The research samples are 40 students taken from two schools, mainly SMA Semesta Semarang and SMA Negeri 8 Semarang. The questionnaire was used as the data collection method. The validity used is the validity construct and the reliability of this instrument with the alpha formula. The result shows that the attitude of students in high school towards French language learning was good. Based on the attitude component, the cognitive component had the highest yield at 35.8%, while the affective component was 32.7%, and the conative component was 31.5%. The cognitive component contains the knowledge and benefits of studying French in the future.